2004
DOI: 10.1080/10647440500068289
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bordetella pertussis Antibodies in Mothers and their Newborn Infants

Abstract: BACKGROUND: Pertussis is a highly communicable, vaccine-preventable respiratory disease. Although the largest number of reported cases is among young infants, the most rapidly increasing incidence in the USA is in adolescents and young adults. Importantly, adult family members are the likely major reservoir, infecting susceptible infants before completion of childhood vaccination. We studied maternal-neonatal paired blood samples for the presence of pertussis-related antibodies to assess level of immunity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 9 publications
6
30
1
2
Order By: Relevance
“…This significant relationship between maternal anti-PT with neonatal cord blood was confirmed by Gonik et al (17). Moreover, it has been shown that in spite of the highly efficient placental antibodies transportation, IgG concentrations are not high enough to passively protect neonates in the first months of life (1).…”
Section: Discussionsupporting
confidence: 55%
“…This significant relationship between maternal anti-PT with neonatal cord blood was confirmed by Gonik et al (17). Moreover, it has been shown that in spite of the highly efficient placental antibodies transportation, IgG concentrations are not high enough to passively protect neonates in the first months of life (1).…”
Section: Discussionsupporting
confidence: 55%
“…In particular, CD4 ϩ T cells and the presence of gamma interferon seem to be important for the clearance of bacteria from the lung (31). Furthermore, B cells can also represent a source of cytokines and chemokines, which in turn can exert a critical regulatory effect on APCs and CD4 ϩ -T-cell-mediated immunity (5,17,32). Although we have not directly addressed the role of cell-mediated immunity in the present study, we believe that a combination of both humoral and cell-mediated immunity is required for optimal disease protection.…”
Section: Discussionmentioning
confidence: 99%
“…63 Further studies since 2000 demonstrated that both naturally and vaccine-induced pertussis-specific IgG in mothers was efficiently transported across the placenta, resulting in higher infant than maternal antibody levels for tested pertussis antigens. [64][65][66][67][68] Van Savage et al had calculated the half-life (t 1/2 ) of naturally-induced maternal antibody to PT and FHA to be 36 and 40 days, respectively. 69 Serological correlates of protection from pertussis are not known.…”
Section: Immune Response Following Pertussis Immunization In Pregnancymentioning
confidence: 99%